INTENTION TO REDUCE SUGAR CONSUMPTION OF SUGAR-SWEETENED BEVERAGES (SSB) - Wan Rusni binti Wan Ismail; Wan Hayati binti Wan Bujang; Norliana binti Hashim; Firdaus Ahmad Fauzi; Nashwa binti Abdul Ghani (Journal of Islamic, Social, Economics and Development, 2022)
Sugar is an important source of energy. However, sugar consumption among Malaysians has been increasing due to urbanization and marketing strategy. Today, Malaysia holds the the highest record of obesity rates among adults in South Asian Countries. It has raised concern on the side effects that could affect well-being due to consumption of SSB. Therefore, this quantitative study aimed to reveal factors that influences intention to reduce sugar consumption in SSB among Malaysians. Survey questions was distributed to Malaysian above 18 years old through social media platforms. A cumulative number of 268 respondents was successfully collected but only 201 responses were considered as valid. The study has found that age group plays an important role in shifting lifestyle. Younger age group are unlikely intend to reduce sugar consumption as there are barrier that could not be avoided. It can also be said that they do not feel threaten or at risk of the consequences in consuming SSB. Thus, intention to reduce sugar consumption relies entirely on individuals’ perception towards the threats, risk and benefits. The study conclude that it is crucial to create awareness on the side effects of consuming SSB towards health especially to younger generations as they perceived the most barriers.